MEMAHAMI KORUPSI DI DAERAH PASCA DESENTRALISASI: BELAJAR DARI EMPAT STUDI KASUS - Budi Setiyono (Politika: Jurnal Ilmu Politik, 2017)
Since ‘reformasi movement’ and decentralization takes place, a lot of local government officials (politicians and bureaucrats) are jailed due to their involvement in corruption cases. While on the one hand, this may an evidence that corruption eradication efforts have shown positive results, but on the other hand, it leaves ironic heartbreaking questions. Why these officials caught in corruption cases? Are they economically shortage that forced them to illegally "steal the state money" for themself, their family, as well as their patrons? Or is it related to the wider socio-political context that they can not control? This paper shows that the causes, patterns and modes of corruption at local level were very diverse. In addition to factors related to moral hazard, corruption is also associated with poor government administration, convoluted and unclear regulations, rigid organizational hierarchy, and political rivalry that can lead to an entrapment of official in actions that are perceived as corrupt. These conditions are exacerbated by the weakness of the behavior and commitment of law enforcement agencies in combating corruption. It is urgent, therefore, to develop an integrated system and strategy to increase the effectiveness of corruption eradication. We need to form an a comprehensive policy of combating corruption which is based on the principle of accountability and public participation.Keywords: local government corruption, anti-corruption measures, accountability, governance.